Systematic Mapping Study on Natural Language Processing for Social Robots - Adem, Aysu İrem and Turhan, Çiğdem and Sezen, Arda (International Journal of Computational and Experimental Science and Engineering, 2024)
Nowadays, social robots are becoming increasingly sophisticated in terms of their ability to interact with humans and possess social skills, and in this context, natural language processing (NLP) plays a critical role for robots to understand and communicate with human language. Natural Language Processing (NLP) is an interdisciplinary field used to help computers understand, interpret, and generate human language with a wide range of applications. The examination of the datasets, methods/techniques and tools, and usage of speech recognition or generation in the fields of NLP is important in understanding the developments in this field. In this study, 35 out of 92 studies in the literature collected from Web of Science were examined using a systematic mapping approach, and important findings on the use of NLP in social robots were identified. In particular, emphasis was placed on the effective evaluation of the research questions in the context of NLP in social robots. This study creates a starting point that will guide research in the field of NLP use in social robots and guide future studies.